Landing forces in volleyball spiking and blocking - Coleman, S. G. S.; Lobietti, R. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The present study sought to investigate Vertical Ground Reaction Forces during landings from volleyball spiking and blocking actions. 16 players from Scottish Division 1 and 2 teams performed 10 spikes, 10 blocks from the right and 10 from the left, landing on two Kistler force plates. Kinematic data were also obtained using a 6-camera Qualisys motion capture system. The spike resulted in significantly larger VGRF than either of the blocks, probably due to the greater maximum height attained in the jump. Analysis of the significant interaction between action and feet showed that in the block to the right, the right foot experienced a significantly larger VRGF than the left. There were large inter-individual differences and coaches need to examine techniques closely before making recommendations about landings.